Multiple familial trichoepithelioma: A case report - Mathur, M; Kedia, SK (Journal of College of Medical Sciences-Nepal, 2012)
Trichoepithelioma are benign epidermal appendageal tumour with follicular differentiation. Tumor has been categorized into solitary, multiple and desmoplastic types. The multiple familial trichoepithelioma is autosomal dominant inheritance and rarely seen. Journal of College of Medical Sciences-Nepal,2011,Vol-6,No-4, 64-68 DOI: http://dx.doi.org/10.3126/jcmsn.v6i4.6731